Resin composition, adhesive film, millimeter wave substrate, millimeter wave radar substrate, printed wiring board, and semiconductor device

JP7641038B2Active Publication Date: 2025-03-06NAMICS CORPORATION
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023167871
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-12-04
Filing Date
2023-09-28
Publication Date
2025-03-06
Estimated Expiration
2039-12-02

AI Technical Summary

Benefits of technology

【0011】 本発明〔1〕によれば、樹脂組成物の硬化物が高周波特性に優れ、tanδの温度依存性が小さく、かつ難燃性に優れる、ミリ波基板用の絶縁体として使用することが可能なミリ波基板用樹脂組成物を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007641038000001
    Figure 0007641038000001
  • Figure 0007641038000002
    Figure 0007641038000002
  • Figure 0007641038000003
    Figure 0007641038000003
Patent Text Reader

Abstract

To provide a resin composition which is usable as an insulator such as a millimeter wave substrate that provides a cured product of the resin composition excellent in high frequency characteristics, has small temperature dependency of tanδ, and is excellent in flame retardancy.SOLUTION: A resin composition contains a flame retardant containing a phosphinic acid metal salt, wherein the relative dielectric constant at 10 GHz and 25°C of its cured product is 3.5 or less, the dielectric loss tangent at 10 GHz and 25°C of the cured product is 0.003 or less, and a change rate of a value at 120°C to a value at 25°C of the dielectric loss tangent at 10 GHz of the cured product is 30% or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition, an adhesive film, a millimeter wave substrate, a millimeter wave radar substrate, a printed wiring board, and a semiconductor device. [Background technology]

[0002] Generally, printed wiring boards for high frequency applications are required to have low transmission loss. In the past, low transmission loss in the 1 GHz band was sufficient even for high frequency applications, and it was not considered a problem if the dielectric tangent (tan δ), which is an index of the degree of transmission loss, was at the level of 0.01 or less in the adhesive layer, coverlay, or substrate of the printed wiring board. For this reason, some fluctuation (drift) in the value of tan δ due to temperature changes was tolerated. For example, when the value of tan δ at room temperature is 0.0100 and the value at high temperature is 0.0110, the amount of change is 0.0010, and the rate of change of tan δ is within 10%.

[0003] However, in recent years, there has been a demand for characteristics in the high frequency band of 3 GHz or more, and in order to reduce transmission loss, smaller values ​​of tan δ, for example, 0.003 or less, are required. As a result, even a slight change in the value of tan δ results in a large rate of change in tan δ; for example, when the value of tan δ at room temperature is 0.0030 and the value at high temperature is 0.0040, the amount of change is 0.0010, but the rate of change in tan δ is as large as 33.3%. For this reason, there is a demand for materials with a smaller rate of change in tan δ due to temperature change.

[0004] In particular, for millimeter-wave circuit boards (hereafter referred to as millimeter-wave boards), the frequency band is even higher, and the requirement that the rate of change of tan δ due to temperature change be small (i.e., that the temperature dependency of tan δ be small) becomes even stricter. There are similar strict requirements for automotive millimeter-wave radars that use millimeter-wave radar boards (hereafter referred to as millimeter-wave radar boards).

[0005] In addition, for circuit board applications, in addition to the requirement that the temperature dependence of tan δ be small, flame retardancy may also be required. In such cases, the use of flame retardants is necessary, but currently, halogen-free flame retardants are a prerequisite, and halogen-based flame retardants cannot be used.

[0006] Here, as "a resin composition for printed wiring boards which exhibits excellent dielectric properties in the high frequency band, little drift of the dielectric properties with respect to temperature change, and excellent stability" (paragraphs 0012 and 0015 of Patent Document 1, etc.), there is disclosed "a resin composition for printed wiring boards which is characterized by containing a cyanate ester compound having two or more cyanate groups in the molecule and / or a prepolymer thereof, and an epoxy resin containing at least one epoxy resin having a biphenyl skeleton in the molecule" (Patent Document 1).

[0007] However, this resin composition for printed wiring boards has a high relative dielectric constant (ε) of 3.5 or more and a high tan δ of 0.004 or more at 25°C, so that even if the temperature dependency of tan δ is small, it is difficult to use it for millimeter wave boards. In addition, the flame retardant specifically disclosed is a halogen-based flame retardant. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2010-212689 A Summary of the Invention [Problem to be solved by the invention]

[0009] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a resin composition for millimeter wave substrates, which can be used as an insulator for millimeter wave substrates, and which provides a cured product of the resin composition having excellent high-frequency characteristics, small temperature dependence of tan δ, and excellent flame retardancy. [Means for solving the problem]

[0010] The present invention relates to a resin composition for millimeter wave substrates, an adhesive film for millimeter wave substrates, a millimeter wave substrate, a millimeter wave radar substrate, and a semiconductor device, which have the following configurations and thereby solve the above problems. [1] A resin composition comprising: (A) a hydrogenated styrene-based elastomer; (B) a crosslinkable compound having a biphenyl skeleton; and (C) a flame retardant containing a metal phosphinate, the amount of the component (C) is 15 parts by mass to 50 parts by mass per 100 parts by mass of the total of the components (A), (B), and (C); A resin composition for millimeter wave substrates, characterized in that the rate of change in dielectric tangent at 10 GHz of the cured product at 120°C from the value at 25°C is 30% or less. [2] The resin composition for millimeter wave substrates according to the above [1], wherein the metal phosphinate of the component (C) is 5 parts by mass or more. [3] The dielectric loss tangent at 10 GHz is 0.0030 or less, as described in [1] or [2] above. The resin composition for millimeter wave substrates described above. [4] The resin composition for millimeter wave substrates according to any one of the above [1] to [3], wherein the (A) component is 50 to 80 parts by mass per 100 parts by mass of the total of the (A) component and the (B) component. [5] The resin composition for millimeter wave substrates according to any one of the above [1] to [4], wherein the component (A) is a styrene-ethylene / butylene-styrene block copolymer. [6] An adhesive film for millimeter wave substrates, comprising the resin composition for millimeter wave substrates according to any one of [1] to [5] above. [7] A millimeter wave substrate comprising a cured product of the resin composition for a millimeter wave substrate according to any one of [1] to [5] above. [8] A millimeter wave radar substrate comprising a cured product of the resin composition for millimeter wave substrates according to any one of [1] to [5] above. [9] A semiconductor device including the millimeter wave substrate according to [7] above, or the millimeter wave radar substrate according to [8] above. Effect of the Invention

[0011] According to the present invention [1], it is possible to provide a resin composition for millimeter wave substrates, which can be used as an insulator for millimeter wave substrates, and which has excellent high frequency characteristics, small temperature dependence of tan δ, and excellent flame retardancy when cured.

[0012] According to the present invention [7], it is possible to provide a millimeter wave substrate having excellent high frequency characteristics, small temperature dependence of tan δ, and excellent flame retardancy. According to the present invention [8], it is possible to provide a millimeter wave radar substrate having excellent high frequency characteristics, small temperature dependence of tan δ, and excellent flame retardancy.

[0013] According to the present invention [9], it is possible to provide a highly reliable semiconductor device including a millimeter-wave substrate or a millimeter-wave radar substrate (hereinafter also referred to as a substrate) having excellent high-frequency characteristics, small temperature dependence of tan δ, and excellent flame retardancy. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Preferred embodiments of the present invention will be described in detail below. However, the present invention is not limited to the following embodiments. In this specification, the frequency range used for the millimeter wave board and the millimeter wave radar board is 3 GHz to 300 GHz.

[0015] [Resin composition for millimeter wave substrate] The resin composition for a millimeter wave substrate (hereinafter referred to as a substrate resin composition) of the present invention is a resin composition containing (A) a hydrogenated styrene-based elastomer, (B) a crosslinkable compound having a biphenyl skeleton, and (C) a flame retardant containing a metal phosphinate, the (C) component is 5 parts by mass to 50 parts by mass per 100 parts by mass of the total of the (A) component, the (B) component, and the (C) component; The cured product is characterized in that the rate of change in dielectric tangent at 10 GHz at 120°C from the value at 25°C is 30% or less.

[0016] The hydrogenated styrene-based elastomer, which is the component (A), contributes to film properties, heat resistance, and the like. It also imparts excellent electrical properties, low dielectric constant, and low dielectric tangent in the high frequency band. Furthermore, the temperature dependency of tan δ is small. The component (A) also has a moderate flexibility that allows the resin composition for substrates after curing to relieve external stress, so that it can relieve stress generated within the substrate. Examples of the component (A) include styrene-ethylene / butylene-styrene block copolymer (SEBS), styrene-ethylene / propylene-styrene block copolymer (SEPS), and styrene-(ethylene-ethylene / propylene)-styrene block copolymer (SEEPS), and from the viewpoint of heat resistance, styrene-ethylene / butylene-styrene block copolymer (SEBS) is preferred. The weight average molecular weight of the component (A) is preferably 30,000 to 200,000. The weight average molecular weight is a value obtained by gel permeation chromatography (GPC) using a calibration curve of standard polystyrene. The component (A) may be used alone or in combination of two or more kinds.

[0017] The crosslinkable compound having a biphenyl skeleton, which is the component (B), can increase the Tg of the cured product and can prevent the resin composition for substrates from changing over time after curing, thereby maintaining the long-term reliability of the substrate. In addition, the temperature dependency of tan δ is small. Examples of the crosslinkable compound having a biphenyl skeleton include a polyether compound having a phenyl group bonded to a vinyl group at both ends (hereinafter referred to as modified PPE), an epoxy resin having a biphenyl skeleton, and the like. Modified PPE and epoxy resins having a biphenyl skeleton have a small number of hydrophilic groups in the resin, so that they have low hygroscopicity and excellent moisture resistance. In addition, these have excellent insulating properties, and even if the thickness of the substrate formed from the resin composition for substrates is reduced, the reliability of the substrate can be maintained.

[0018] As a polyether compound having a phenyl group bonded to a vinyl group at both ends, there is a compound represented by the general formula (1):

[0019] [ka]

[0020] [ka]

[0021] (In the formula, R1, R2, R3, R4, R5, R6, and R7 may be the same or different and are a hydrogen atom, a halogen atom, an alkyl group, a halogenated alkyl group, or a phenyl group; -(OXO)- is represented by the structural formula (2), where R8, R9, R 10 , R 14 , R 15 may be the same or different and are a halogen atom, an alkyl group having 6 or less carbon atoms, or a phenyl group; R 11 , R 12 , R 13 may be the same or different and are a hydrogen atom, a halogen atom, an alkyl group having 6 or less carbon atoms, or a phenyl group, -(YO)- is one type of structure represented by structural formula (3) or two or more types of structures represented by structural formula (3) arranged randomly, where R 16 , R 17 may be the same or different, and each is a halogen atom, an alkyl group having 6 or less carbon atoms, or a phenyl group; R 18 , R 19 may be the same or different and are a hydrogen atom, a halogen atom, an alkyl group having 6 or less carbon atoms, or a phenyl group, Z is an organic group having one or more carbon atoms, which may optionally contain an oxygen atom, a nitrogen atom, a sulfur atom, or a halogen atom; a and b are integers from 0 to 300, at least one of which is not 0; and c and d each represent an integer of 0 or 1) (hereinafter referred to as modified PPE).

[0022] In the structural formula (2) of -(OXO)- of the modified PPE represented by the general formula (1), R8, R9, R 10 , R 14 , R 15 is preferably an alkyl group having 3 or less carbon atoms, and R11 , R 12 , R 13 is preferably a hydrogen atom or an alkyl group having a carbon number of 3 or less. Specific examples include structural formula (4).

[0023] [ka]

[0024] In the structural formula (3) for -(YO)-, R 16 , R 17 is preferably an alkyl group having 3 or less carbon atoms, and R 18 , R 19 is preferably a hydrogen atom or an alkyl group having a carbon number of 3 or less. Specific examples include structural formula (5) or (6).

[0025] [ka]

[0026] Z is an alkylene group having 3 or less carbon atoms, specifically a methylene group.

[0027] At least one of a and b is not 0, and represents an integer of 0 to 300, preferably an integer of 0 to 30.

[0028] The modified PPE of general formula (1) preferably has a number average molecular weight of 1000 to 4500. The number average molecular weight is more preferably 1000 to 3000. The above modified PPE may be used alone or in combination of two or more kinds.

[0029] An epoxy resin having a biphenyl skeleton is preferred from the viewpoints of improving the adhesive strength of the resin composition for substrates and reducing the temperature dependency of tan δ compared to epoxy resins having other structures. In addition, it is preferred that the epoxy equivalent is 150 to 300 and does not contain a hydroxyl group in the molecule. However, an epoxy resin having a biphenyl skeleton may not be included. In one embodiment, the resin composition for substrates does not substantially contain an epoxy resin.

[0030] It is preferable that the (B) component further contains an initiator or a curing agent. Examples of initiators for modified PPE include organic peroxides, and examples of curing agents for epoxy resins having a biphenyl skeleton include phenol-based curing agents, amine-based curing agents, imidazole-based curing agents, and acid anhydride-based curing agents. In particular, imidazole-based curing agents are preferable from the viewpoints of curing properties, adhesiveness, and reducing the temperature dependence of tan δ for epoxy resins having a biphenyl skeleton. The (B) component may be used alone or in combination of two or more kinds.

[0031] As the flame retardant containing a metal phosphinate as component (C), there is e (POOR 20 R 21 ) f (wherein M is Li, Na, K, Mg, Ca, Sr, Ba, Al, Ge, Sn, Sb, Bi, Zn, Ti, Zr, Mn, Fe, or Ce; R 20 , R 21 each represents an aliphatic hydrocarbon group or an aromatic hydrocarbon group having 1 to 5 carbon atoms, and e and f are integers of 1 to 9. Among these, from the viewpoints of flame retardancy and reducing the temperature dependency of tan δ, aluminum phosphinate is preferred, aluminum dialkylphosphinate is more preferred, and aluminum diethylphosphinate is further preferred.

[0032] Flame retardants that can be used as component (C) other than metal phosphinates include non-halogen flame retardants with small temperature dependence of tan δ. Specific examples include biphenol bis-dixylenyl phosphate, 10-(2,5-dihydroxyphenyl)-10-H-9-oxa-10-phosphaphenanthrene-10-oxide, etc. Component (C) may be used alone or in combination of two or more.

[0033] The amount of component (A) is preferably 50 to 80 parts by mass, and more preferably 55 to 80 parts by mass, per 100 parts by mass of the total of components (A) and (B). When the content of component (A) is equal to or greater than the content of component (B), the peel strength of the resin composition for substrates tends to be high, and the heat resistance reliability (for example, 1000 hours or more at 125°C) tends to be improved.

[0034] Furthermore, the amount of the (A) component is preferably 32.5 to 70 parts by mass, more preferably 40 to 70 parts by mass, and even more preferably 40 to 64 parts by mass, per 100 parts by mass of the total of the (A), (B), and (C) components.

[0035] From the viewpoints of imparting flame retardancy and high frequency characteristics, the amount of the component (C) is 15 to 50 parts by mass per 100 parts by mass of the total of the components (A), (B) and (C).

[0036] When the component (C) is only a metal phosphinate, the amount of the metal phosphinate is preferably 20 to 35 parts by mass per 100 parts by mass of the total of the components (A), (B), and (C).

[0037] When component (C) is composed of a metal phosphinate and other flame retardants, it is preferable from the viewpoints of flame retardancy, high frequency characteristics, adhesion, and heat resistance that the metal phosphinate is 5 parts by mass or more and less than 15 parts by mass, the other flame retardants are 20 to 40 parts by mass, and the total amount of the flame retardants which are component (C) is 25 to 50 parts by mass, relative to 100 parts by mass of the total of components (A), (B), and (C).

[0038] The resin composition for substrates may contain additives such as inorganic fillers, silane coupling agents, defoamers, dispersing agents, antioxidants, defoamers, leveling agents, thixotropic agents, antiblooming agents, and antiblocking agents, as well as organic solvents, within the range that does not impair the effects of the present invention.

[0039] As the inorganic filler, from the viewpoint of improving the physical properties of the cured product, a general inorganic filler can be used. From the viewpoint of low thermal expansion coefficient, SiO2 is preferable, and from the viewpoint of obtaining the desired physical properties of the cured product, at least one inorganic filler selected from the group consisting of talc, kaolin, BaSO4, CaCO3, MgO, Al2O3, SiO2, AlN, BN, diamond filler, ZnO, and SiC is preferable. These fillers may be surface-treated.

[0040] The average particle size of the inorganic filler (if not granular, its average maximum diameter) is not particularly limited, but is preferably 0.05 to 20 μm in order to prevent a decrease in moisture resistance of the resin cured product due to moisture absorption on the surface of the filler particles and to obtain a coating film of a desired thickness. If the average particle size of the inorganic filler is less than 0.05 μm, the specific surface area is large, so the amount of moisture absorbed by the inorganic filler surface increases, and the moisture resistance of the resin cured product may deteriorate. If it exceeds 20 μm, it is too large for the required thickness of the coating film, and the desired thickness may not be obtained. Furthermore, when used on a substrate with a fine pattern, the filler is too large for the size of the pattern, so the filler material and the resin are localized on the pattern, and the dielectric loss may increase. The average particle size of the inorganic filler is more preferably 1 to 10 μm, and further, the maximum particle size is preferably 10 μm or less. By making the maximum particle size 10 μm or less, it is easy to prevent an increase in dielectric loss in a frequency band of 10 GHz or more. Here, the average particle size and maximum particle size of the inorganic filler are measured by a laser scattering diffraction type particle size distribution measuring device. The inorganic filler may be used alone or in combination of two or more kinds.

[0041] Examples of the organic solvent include aromatic solvents such as toluene and xylene, ketone solvents such as methyl ethyl ketone and methyl isobutyl ketone, and high boiling point solvents such as cyclohexanone, dimethylformamide, and 1-methyl-2-pyrrolidone. The organic solvent may be used alone or in combination of two or more. The amount of the organic solvent used is not particularly limited, and may be adjusted to provide a preferred viscosity depending on the application method of the resin composition. Specifically, the organic solvent may be used so that the solid content is 20 to 80 mass%.

[0042] The resin composition for substrates can be obtained by dissolving or dispersing raw materials including components (A) to (C) in an organic solvent. The device for dissolving or dispersing these raw materials is not particularly limited, but may be a stirrer equipped with a heating device, a dissolver, a mortar and pestle machine, a three-roll mill, a ball mill, a planetary mixer, a bead mill, or the like. These devices may also be used in appropriate combination.

[0043] The resin composition for substrates can be thermally cured, for example, at 130 to 220° C. for 30 to 180 minutes. The resin composition for substrates can be appropriately selected according to the desired application method from those having a viscosity of 0.1 to 100 Pa s measured at 10 rpm and 25° C. using an E-type viscometer.

[0044] The resin composition for substrates has a rate of change of tan δ at 120°C from the value at 25°C at 10 GHz of the cured product of 30% or less. If the rate of change of tan δ at 120°C from the value at 25°C at 10 GHz is more than 30%, the market demand is not met. The rate of change of tan δ at 120°C from the value at 25°C at 10 GHz is preferably 20% or less, and more preferably 10% or less.

[0045] From the viewpoint of use in that frequency band, the resin composition for substrates preferably has a dielectric loss tangent of 0.0030 or less at 10 GHz. The resin composition for substrates can be used in adhesive layers and coverlays of wiring boards, or in the substrate itself.

[0046] [Products using the resin composition for millimeter wave substrates] The adhesive film for a millimeter wave substrate of the present invention contains the above-mentioned resin composition for a millimeter wave substrate. This adhesive film for a millimeter wave substrate is formed from the resin composition for a substrate.

[0047] The adhesive film for millimeter wave substrates is obtained by applying the resin composition for substrates to a desired support and then drying it. The support is not particularly limited, and examples thereof include metal foils such as copper and aluminum, and organic films such as polyester resins, polyethylene resins, and polyethylene terephthalate resins. The support may be subjected to a release treatment with a silicone compound or the like.

[0048] The method of applying the resin composition for substrates to a support is not particularly limited, but from the viewpoint of thinning and controlling the film thickness, the microgravure method, the slot die method, and the doctor blade method are preferred. By the slot die method, an adhesive film for millimeter wave substrates having a thickness of, for example, 10 to 300 μm after heat curing can be obtained.

[0049] The drying conditions can be appropriately set according to the type and amount of the organic solvent used in the resin composition for the substrate, the thickness of the coating, etc., and can be, for example, 50 to 120°C and about 1 to 30 minutes. The insulating adhesive film for the millimeter wave substrate obtained in this manner has good storage stability. The adhesive film for the millimeter wave substrate can be peeled off from the support at a desired timing.

[0050] The adhesive film for millimeter wave substrates can be thermally cured, for example, at 130 to 220° C. for 30 to 180 minutes.

[0051] The thickness of the adhesive film for millimeter wave substrates is preferably 10 μm or more and 300 μm or less, and more preferably 20 μm or more and 200 μm or less. If it is less than 10 μm, the desired insulation properties, strength and durability of the coating film may not be obtained. If it exceeds 300 μm, the stress during curing may become large, causing problems such as warping of the substrate.

[0052] The millimeter wave substrate of the present invention includes a cured product of the above-mentioned resin composition for a millimeter wave substrate, that is, a cured product of the above-mentioned adhesive film for a millimeter wave substrate.

[0053] The millimeter-wave radar substrate of the present invention includes a cured product of the above-mentioned resin composition for a millimeter-wave substrate, that is, a cured product of the above-mentioned adhesive film for a millimeter-wave substrate.

[0054] A semiconductor device according to the present invention includes the above-mentioned millimeter wave substrate or the above-mentioned millimeter wave radar substrate. EXAMPLES

[0055] The present invention will be described with reference to examples, but the present invention is not limited thereto. In the following examples, parts and % indicate parts by mass and % by mass, unless otherwise specified.

[0056] The raw materials used in the Examples and Comparative Examples shown in Tables 1 to 3 are shown below. G1652MU: Kraton Polymers hydrogenated styrene elastomer SEBS OPE-2St 2200: Styrene-terminated PPE oligomer (molecular weight: Mn2200) manufactured by Mitsubishi Gas Chemical YX4000HK: Biphenyl-based epoxy resin made by Mitsubishi Chemical OP935: Al diethylphosphinate manufactured by Clariant Chemicals, represented by the following chemical formula: Minium (aluminum phosphinate):

[0057] [ka]

[0058] KBE-846: Shin-Etsu Chemical's silane coupling agent, bis(triethoxysilylpropyl)tetrasulfide KBM-573: Shin-Etsu Chemical's silane coupling agent, N-phenyl-3-aminopropyltrimethoxysilane Percumyl D: Dicumyl peroxide, an organic peroxide made by Nippon Oil & Fats EH-2021: ADEKA modified imidazole FB-3SDX: Denka spherical silica filler (average particle size: 3.4 μm) PX-200: Resorcinol bis-dixylenyl phosphate manufactured by Daihachi Chemical Industry Co., Ltd., represented by the following chemical formula:

[0059] [ka]

[0060] PX-202: Biphenol bis-dixylenyl phosphate manufactured by Daihachi Chemical Industry Co., Ltd., represented by the following chemical formula:

[0061] [ka]

[0062] TPP: Triphenyl phosphate manufactured by Daihachi Chemical Industry and represented by the following chemical formula:

[0063] [ka]

[0064] FP-600: ADEKA Bisphenol A bis-diphenyl phosphate, represented by the following chemical formula:

[0065] [ka]

[0066] FP-100: Phenoxycyclophosphazene manufactured by Fushimi Pharmaceutical Co., Ltd., represented by the following chemical formula:

[0067] [ka]

[0068] HCA-HQ-HS: 10-(2,5-dihydroxyphenyl)-10-H-9-oxa-10-phosphaphenanthrene-10-oxide manufactured by Sanko and represented by the following chemical formula:

[0069] [ka]

[0070] HCA: 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide manufactured by Sanko and represented by the following chemical formula:

[0071] [ka]

[0072] TR2003: JSR non-hydrogenated styrene elastomer SBS

[0073] [Examples 1 to 10 , Comparative Example 1~ 8、10~ 11) After weighing each component in the formulation (parts by mass) shown in Tables 1 to 3, the (A) or (A') component and the (B) component were put into a heated mixer to which a predetermined amount of toluene had been put beforehand, and dissolution and mixing were performed for 2 hours at 70°C and normal pressure while rotating the stirring blade at a rotation speed of 35 rpm. After that, after cooling to room temperature, the (C) component, the (C') component and other components were put in, and the stirring blade was rotated at a rotation speed of 60 rpm, and stirring and mixing were performed for 1 hour. Next, a predetermined amount of toluene was added to the stirred product so that the viscosity was suitable for coating, and the mixture was diluted by stirring. After that, the resin composition was dispersed using a wet type atomizer (manufactured by Yoshida Kikai Kogyo Co., Ltd., model number: Nanomizer MN2-2000AR).

[0074] The coating liquid containing the resin composition thus obtained was applied to one side of a support (a PET film subjected to a release treatment) and dried at 100°C to obtain an adhesive film for millimeter wave substrates (thickness 100 μm) with a support.

[0075] [1. Flame retardancy evaluation] The test was conducted according to the UL94 VTM combustion test method, and the flame retardancy was judged. The obtained adhesive film for millimeter wave board was heated and cured at 200°C for 60 minutes at 10 kgf, peeled off from the support, and then cut into a size of 200 ± 5 mm in length × 50 ± 1 mm in width to prepare a test piece. The 50 mm side of the test piece was set as the base, and a line was drawn with a pen along the width at a position 125 mm from the base, and a rod with a diameter of 12.7 ± 0.5 mm was applied to the longitudinal direction of the test piece to wrap the test piece, and the part above the line was attached with pressure-sensitive tape, and then the rod was removed, and the upper end of the cylindrical test piece was closed with pressure-sensitive tape to prevent the chimney effect. The upper end of the test piece was gripped with a clamp set on the stand, and the test piece was held vertically. A Bunsen burner with an inner diameter of 9.5±0.3 mm (0.374±0.012 inches) was ignited, and the flame was adjusted so that it was a blue flame without yellow and had a height of 19 mm (3 / 4 inches). This flame was held at the center of the lower end of the cylindrical test piece so that the distance from the burner nozzle was 9.5 mm (3 / 8 inches), and the first flame contact was performed for 3±0.5 seconds, then the test piece was removed, and the burning time (including the ignition time) of the test piece was measured. Immediately after the flame was extinguished, the test piece was exposed to the flame for 3±0.5 seconds, then the test piece was removed, and the burning time (including the ignition time) was measured. Tests were performed with five test pieces for each of the examples and comparative examples, and those that met the VTM-0 judgment conditions shown below were judged to be equivalent to VTM-0 and passed, and the results were expressed as "○" for those that were equivalent to VTM-0 and "×" for those that were not.

[0076] <VTM-0 Judgment Criteria> (1) The burning time of each test specimen after the first or second flame release is 10 seconds or less. (2) The total of the first and second burning times of the five test specimens is 50 seconds or less. (3) The total burning time after the second flame separation is 30 seconds or less. (4) The combustion does not reach the ballot line. (5) There is no ignition of absorbent cotton (placed below the test specimen) due to falling objects during combustion. *However, since nothing fell during combustion, no attention was paid to the ignition of the absorbent cotton.

[0077] [2. Evaluation of relative dielectric constant (ε) and dielectric tangent (tan δ)] After peeling the adhesive film for millimeter wave substrates from the support, it was laminated to a thickness of about 1 mm, and after heat curing at 200°C for 60 minutes at 10 kgf, it was cut to a width of about 1 mm and a length of about 20 mm to obtain a rod-shaped test piece. The dimensions of this test piece were measured, and the relative dielectric constant (ε) and dielectric loss tangent (tan δ) at 10 GHz and 25°C were measured using a cavity resonator in a precision thermostatic chamber. It is preferable that the relative dielectric constant is 3.5 or less, and the dielectric loss tangent is 0.003 or less.

[0078] [3. Evaluation of temperature dependence (temperature characteristics) of dielectric constant (ε) and dielectric tangent (tan δ)] The test pieces prepared in [2. Evaluation of relative dielectric constant (ε) and dielectric loss tangent (tan δ)] were placed in a precision thermostatic chamber heated to 120°C and the relative dielectric constant (ε) and dielectric loss tangent (tan δ) at 10 GHz and 120°C were measured using a cavity resonator. From these values, the percent change relative to the measured value at 25°C was calculated. It is preferable that the percent change is ±30% or less.

[0079] 4. Evaluation of Peel Strength Copper foil (CF-T9FZSV, manufactured by Fukuda Metal Foil & Powder Co., Ltd., thickness: 18 μm) was attached to both sides of the adhesive film for millimeter wave substrates with the roughened surface facing inward, and the film was press-cured at 200°C for 60 minutes at 30 kgf using a press machine. The test piece was cut to a width of 10 mm, peeled off from the interface with the copper foil using an autograph, and the 180° peel strength was measured (in accordance with JIS K6854-2). The average value of n=5 was taken as the measured value. It is preferable that the peel strength is 4.5 (unit: (N / cm)) or more.

[0080] [5. Evaluation of solder heat resistance] As in [4. Evaluation of peel strength], the copper foil was laminated and cured, then cut into 30 x 30 mm test pieces. These were placed on the surface of a solder bath heated to 260°C for 60 seconds, and the occurrence of blisters was visually observed. n=3 tests were performed, and those that did not blisters were marked with "○" and those that did blisters were marked with "×".

[0081]

Table 1

[0082]

Table 2

[0083]

Table 3

[0084] Tables 1 to 3 show the formulations and evaluation results of the examples and comparative examples. In Tables 1 to 3, the filler ratio is the volume ratio (Vol%) of the silica filler to all components except toluene, and is calculated assuming that the specific gravity of the silica filler is 2.2 and the specific gravity of the other components is 1.0. The elastomer ratio is the mass ratio (%) of the (A) component to 100 parts by mass of the total of the (A) component and the (B) component. Example 1 was used as the reference formulation. In Example 1, the ratio of the (A) component:(B) component to 100 parts by mass of the total of the (A) component and the (B) component was 65:35, the blending amount of the (C) component was 30 parts by mass to 100 parts by mass of the total of the (A) component, the (B) component, and the (C) component, the blending ratio of the silica filler was 227 parts by mass so that it was 50 vol% (volume %), and KBE-846 (sulfide type) was used as the silane coupling agent. Example 2 is a compound in which the silica filler is omitted from the compounding of Example 1. Example 3 is a compound in which the amount of the (C) component is 20 parts by mass relative to a total of 100 parts by mass of the (A), (B), and (C) components, and a part of the (B) component is replaced with a biphenyl skeleton epoxy resin. The ratio of the (A) component:(B) component is 60:(35:5). Example 4 is a compound in which the amount of the (C) component is 50 parts by mass relative to a total of 100 parts by mass of the (A), (B), and (C) components. Example 5 is a compound in which the amount of the (C) component is 15 parts by mass relative to a total of 100 parts by mass of the (A), (B), and (C) components. Example 6 is a compound in which the amount of the (C) component is 20 parts by mass relative to a total of 100 parts by mass of the (A), (B), and (C) components, and a ratio of the (A) component:(B) component is 80:20. In Example 7, the amount of component (C) was 20 parts by mass relative to 100 parts by mass of the total of components (A), (B), and (C), and the ratio of components (A):(B) was 55:45. In Example 8, the amount of component (C) was 20 parts by mass relative to 100 parts by mass of the total of components (A), (B), and (C), and the other component, the silane coupling agent, was changed to KBM-573 (amino type). In Example 9, two types of flame retardants (C) were used in combination.More specifically, this is an example in which the blending amount of component (C) is 45 parts by mass relative to 100 parts by mass of the total of components (A), (B), and (C), and 5 parts by mass of metal phosphinate is combined with 40 parts by mass of another flame retardant (HCA-HQ-HS).

[0085] As can be seen from Table 1, all of Examples 1 to 9 had good results, including flame retardancy equivalent to VTM-0, low temperature dependence of ε and ε, low temperature dependence of tan δ and tan δ, high peel strength, and high solder heat resistance.

[0086] As can be seen from Table 2, in Comparative Examples 1 to 7, the (C) component of Example 1 was replaced with another phosphorus-based flame retardant ((C') component) at the same content. In all of Comparative Examples 1 to 7, the flame retardancy did not achieve VTM-0 and was inferior to Example 1. However, Comparative Example 2 using PX-202 and Comparative Example 6 using HCA-HQ-HS had a small tan δ value at 25°C and good temperature characteristics (small temperature dependency). However, Comparative Examples 1, 3, 4, 5, and 7 had very poor temperature characteristics (large temperature dependency), and further, Comparative Examples 3, 4, and 5 had tan δ values ​​at 25°C exceeding 0.003, which was at a level that could not be used for millimeter wave substrate applications. Furthermore, Comparative Examples 4 and 7 had low peel strength.

[0087] As can be seen from Table 3, Comparative Example 8, in which the component (A) of Example 1 was replaced with a non-hydrogenated styrene-based elastomer (component (A')), had poor temperature characteristics of tan δ (high temperature dependency). Example 10In Comparative Example 1, the amount of component (C) in Example 1 was 55 parts by mass relative to 100 parts by mass of the total of components (A), (B), and (C), and the solder heat resistance was inferior to that of Example 1, and the peel strength was also low. In Comparative Example 10, the amount of component (C) in Example 1 was 10 parts by mass relative to 100 parts by mass of the total of components (A), (B), and (C), and the flame retardancy did not achieve VTM-0. In Comparative Example 11, component (C) was omitted from Example 1 and no flame retardant was added, and the flame retardancy did not achieve VTM-0. On the other hand, the temperature characteristics were good (temperature dependency was small).

[0088] As described above, the resin composition for millimeter wave substrates of the present invention has excellent high frequency characteristics, small temperature dependence of tan δ, and excellent flame retardancy when cured, and can be used as an insulator for millimeter wave radar. The resin composition is therefore extremely useful for producing highly reliable millimeter wave substrates, millimeter wave radar substrates, and semiconductor devices.

Claims

1. A flame retardant containing a metal phosphinate; A resin containing a hydrogenated styrene-based elastomer (excluding cases containing an epoxy resin and a polyfunctional vinyl aromatic copolymer containing a repeating unit (a) derived from a divinyl aromatic compound and a repeating unit (b) derived from a monovinyl aromatic compound), Including, The content of the flame retardant is 15 parts by mass to 55 parts by mass per 100 parts by mass of the total of the resin and the flame retardant, the cured product has a relative dielectric constant of 3.5 or less at 10 GHz and 25°C; the dielectric tangent of the cured product at 10 GHz and 25° C. is 0.003 or less; A resin composition (excluding a case where a curing agent is contained) characterized in that the rate of change in dielectric tangent at 10 GHz at 120°C relative to the value at 25°C of the cured product is 30% or less.

2. The resin composition according to claim 1, which is for use in a millimeter wave substrate or a printed wiring board.

3. An adhesive film comprising the resin composition according to claim 1 or 2.

4. The adhesive film according to claim 3, having a thickness of 10 to 300 μm.

5. A millimeter wave substrate comprising a cured product of the resin composition according to claim 1 or 2.

6. A millimeter wave radar substrate comprising a cured product of the resin composition according to claim 1 or 2.

7. A printed wiring board comprising a cured product of the resin composition according to claim 1 or 2.

8. A semiconductor device comprising: the millimeter-wave substrate according to claim 5; the millimeter-wave radar substrate according to claim 6; or the printed wiring board according to claim 7.

Citation Information

Patent Citations

  • Resin composition for printed wiring board, and vanish, prepreg and metal-clad laminate using the same

    JP2010212689A

  • Resin composition and an adhesive film and a coverlay film using the same

    JP2014034668A

  • Curable resin composition, cured product of the same, curable composite material, metal foil with resin, and varnish for circuit board material

    JP2018168347A